PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KARYAWAN PT. PLN PERSERO ULP BOMBANA - Muh. Dody Almaruf; Bakhtiar Abbas; Indira Yuana (Sigma: Journal of Economic and Business, 2022)
The research objectives are to identify and analyze; (1) The influence of leadership style and work motivation on employee productivity of PT. PLN Persero ULP Bombana; (2) The influence of leadership style on employee productivity; (3) The effect of work motivation on employee productivity. Population is employees of PT. PLN Persero ULP Bombana, totaling 58 people, not including the leadership, in this case is the Manager of PT. PLN Persero ULP Bombana and at the same time used as respondents in this study. The data analysis method used is quantitative descriptive analysis and multiple linear regression.The results of the study stated that; (1) Leadership style and motivation have a positive and significant effect on employee productivity; (2) leadership style has a positive and significant effect on employee productivity; (3) Motivation has a positive and significant effect on employee productivity